Biocompatibility of TiO2 nanorods and nanoparticles on HeLa Cells - Noor Sakinah Khalid,; Fatin Izyani Mohd Fazli,; Noor Kamalia Abd Hamed,; Muhammad Luqman Mohd Napi,; Soon, Chin Fhong; Mohd Khairul Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Titanium dioxide (TiO2) nanorods and nanoparticles had been successfully done by hydrothermal method and spray pyrolysis deposition technique, respectively. Form XRD results, crystallite structure for TiO2 nanorods is rutile phase at 2θ degree 27.5° which corresponded to [110] orientation. Whereas, TiO2 nanoparticles produced anatase phase at 2θ degree 25.3° which corresponded to [110] plane. The structure of nanorods and nanoparticles were characterized using FESEM. The size of nanorods was in the range of 80 to 100 nm. While, the nanoparticles size was ranging from 25 to 35 nm. The HeLa cells were grown on those TiO2 and were observed under fluorescence microscope. The cells showed healthy sign of growth on TiO2 nanorods and nanoparticles substrates. Thus, TiO2 nanorods and nanoparticles are biocompatible to HeLa cells.